Catholic Church Interiors in Fin-de-Siècle Literature - Claire Masurel-Murray (Cahiers Victoriens et Edouardiens)
The works of such late-Victorian writers as Lionel Johnson, Ernest Dowson, Theodore Wratislaw, John Oliver Hobbes and Oscar Wilde represent Catholic churches as retreats set apart from the ugliness and mediocrity of Victorian England—religious versions of Des Esseintes’s Fontenay-aux-Roses house in À rebours—filled with incense, organ music, and coloured light filtering through medieval stained-glass windows. In Dowson’s correspondence or in his poem ‘Benedictio Domini’, in Johnson’s ‘Our Lady of France’, in Wratislaw’s ‘Palm Sunday’ and ‘Songs to Elizabeth’, in some of Wilde’s stories, the opposition between inside and outside expresses figuratively the fundamental incompatibility between an ideal of beauty, embodied in the aesthetic experience of the church, and the coarseness of the outside world. This article explores how such a polarised vision reflects contemporary debates about the interior organisation and decoration of churches. Drawing on William Whyte’s analyses of changing attitudes towards church architecture in the 19th century in Unlocking the Church: The Lost Secrets of Victorian Sacred Space (OUP 2017), it shows how literary representations of church interiors in fin-de-siècle literature reflect the shift from the Protestant aniconic, congregation-centred approach to church design, in favour of an architecture of affect and sensation, where space and ornamentation lead the worshipper to experience the divine through a sensory overload. It focuses on two aspects of church architecture and decoration that are foregrounded in fin-de-siècle poetry and fiction—and were highly polemical in the late Victorian context because of their association with the Ritualist controversy and with ‘Romishness’: the eastward position, i.e. the celebration of the Eucharist on a stone altar fixed to the back of the chancel rather than on a wooden communion table facing the congregation; and altar candles, which were condemned in anti-ritualist pamphlets as both pagan and ‘popish’. Through these two examples, this article argues that fin-de-siècle literary representations of church interiors reflect a major change in the perception of sacred space, from the ‘auditory church’ (Whyte) of the 18th century, where function (essentially focused on the proclamation of the word of God) dictated the organisation of space and even the furnishings, to the ‘visual church’, saturated with symbolism, where the eye, rather than the ear, becomes the central organ of religious experience.